2021
DOI: 10.1101/2021.02.14.431169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual variability of neural computations in the primate retina

Abstract: Variation in the neural code between individuals contributes to making each person unique. Using ~100 neural population recordings from major ganglion cell types in the macaque retina, we develop an interpretable computational representation of individual variability using machine learning. This representation preserves invariances, such as asymmetries between ON and OFF cells, while capturing individual variation and covariation in properties such as nonlinearity, temporal dynamics, and spatial receptive fie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…One solution to this could be to learn a shared embedding space [see 51], from which domain effects are removed, but distinct encoders f i and decoders g i for different trials i. In another setting, where different stimuli are presented between experiments, one might resort to an approach like Shah et al [3]. Nevertheless, we do acknowledge that the data in our applications consists of ex vivo retinal recordings which have little to no attentional effects or task-dependent noise correlations like they would be present in in vivo cortical data.…”
Section: Limitationsmentioning
confidence: 99%
See 4 more Smart Citations
“…One solution to this could be to learn a shared embedding space [see 51], from which domain effects are removed, but distinct encoders f i and decoders g i for different trials i. In another setting, where different stimuli are presented between experiments, one might resort to an approach like Shah et al [3]. Nevertheless, we do acknowledge that the data in our applications consists of ex vivo retinal recordings which have little to no attentional effects or task-dependent noise correlations like they would be present in in vivo cortical data.…”
Section: Limitationsmentioning
confidence: 99%
“…Other studies have suggested models of neural function that integrate data across experiments. Shah et al [3] build encoding models to predict the responses of retinal ganglion cells across different experiments [see also 13] and compare it to covariates such as the gender of an animal. Sorochynsky et al [14] propose a way to measure noise correlations in each recording and integrate those into models of neural populations of a specific cell type.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations